Preprečevanje, prepričevanje, obžalovanje - Zupančič, Rok (Teorija in praksa, 2016)
The paper analyses US foreign policy and the US government's position on the diplomatic recognition of Slovenia at the beginning of the 1990s. The author analyses the period between 1990, when the Bush Administration fervently opposed the independence of Slovenia (and supported the territorial integrity of communist Yugoslavia), and April 1992, when the US government diplomatically recognised Slovenia. The methodology is based on interviews with some key diplomats in the US government who were engaged in forming and implementing US foreign policy regarding Yugoslavia/Slovenia between 1990 and 1992, interviews with Slovenian diplomats, and an analysis of secondary and primary sources obtained in US archives. The author argues that the conservative view of international affairs and the rigidity of US diplomats, which did not reflect an understanding of the geopolitical changes in the 1990s, significantly contributed to the fact that the USA advocated a non-recognition approach even though the USA, at least declaratively, has been a supporter of democratic changes and the principle of self-determination.
Keywords: 1990-1992; ameriška diplomacija; analiza stališč; Attainment of independence; Diplomatic relations; Diplomatski odnosi; diplomatsko priznanje; Disintegration of Yugoslavia; Foreign policy; Osamosvojitev; Priznanje (Mednarodno pravo); Priznanje države [V4.3]; Razpad SFRJ; Recognition (International law); Recognition of a state [V4.3]; Slovenia; Slovenija; United States; Združene države; Zunanja politika